Efficacy and safety of Laparoscopic Endoscopic Cooperative Surgery (LECS) - a systematic review and meta-analysis - Sara Oliveira de Brito (2022)
Laparoscopic and endoscopic cooperative surgery (LECS) combines the advantages of endoscopy and laparoscopy in order to resect gastric submucosal tumors (SMT's). The aim of this systematic review and meta-analysis was to evaluate the efficacy and safety of LECS in patients with EGJ (esophagogastric junction), gastric and duodenal tumors, as well as compare LECS with pure endoscopic procedures and pure laparoscopic procedures. Three databases were searched: PubMed, Scopus and ISI Web of Knowledge. Efficacy (R0, recurrence) and safety (conversion rate, procedure and hospitalization time, adverse events, mortality) outcomes were extracted and pooled with odds ratio (OR) or mean difference (MD) using a random-effects model. Study quality was assessed with Newcastle-Ottawa Scale and heterogeneity by Cochran's Q test and I2. Subgroup analysis according to location was perfomed for 4 outcomes.This Meta-analysis included 24 studies (all retrospective cohorts). No significant differences were found between LECS and pre-existing techniques (ESD/laparoscopic) regarding any outcomes. However, there was a trend to shorter hospitalization time, longer procedure duration and fewer adverse events in LECS vs laparoscopic techniques. The same trend was seen comparing LECS with ESD. R0 tend to be higher in LECS group. Hospitalization time was significantly shorter in gastric lesions compared to EGJ lesions (mean 7.3 vs 13.7 days, 95% CI 6.6‒7.9 vs 8.9‒19.3, respectively). There were no statistically significant differences in conversion rate, adverse events' rate nor mean procedural time according to location. There was a trend to higher convertion rate and longer procedure durations in EGJ and higher rate of adverse events in duodenal lesions. In conclusion, LECS can be a valid, safe and effective treatment option in patients with EGJ, gastric and duodenal tumors. We consider that treatment choice must be individualized. Prospective studies are needed to assess if LECS is superior to established techniques.